PEMBANGKITAN TEGANGAN MENGGUNAKAN KARBON AKTIF TEMPURUNG KELAPA DENGAN ELEKTROLIT AIR - Tista, Si Putu Gede Gunawan; Santhiarsa, I Gusti Ngurah Nitya; Astawa, Ketut; Tenaya, I Gusti Ngurah Putu; Negara, Komang Metty Trisna (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The generation of electrical energy from fossil fuels is currently running low, besides that it can cause global warming due to gas emissions such as carbon dioxide. Besides that, the development of small portable equipment such as watches, handphones, and cameras, requires batteries with small power. Therefore, environmentally friendly materials on a small scale are needed to generate electricity, one of which is coconut shell-activated carbon. The purpose of this research is to generate a voltage from a model using activated coconut shell carbon with a water-electrolyte. The model consists of a counter electrode-electrode counter. The counter electrodes are varied, namely aluminum, zinc, and copper. The electrode used is coconut shell-activated carbon, while the electrolyte is distilled water. The electrolyte is injected into the model between the electrode and the counter electrode and then given the heat. When the electrolyte is injected into the model, electrostatic forces occur between the functional groups, the pores on the surface of the activated carbon, the counter electrode, and the water-electrolyte, resulting in the release of electrons. The results show that the voltage generated by heating to a temperature rise of ΔT = 54 ͦC is 0.795 volts for aluminum counter electrodes, while zinc reaches 0.597 volts and copper reaches 0.034 volts. While the average thermal sensitivity of the resulting voltage (dV/dT) for aluminum is 47.85707 mV/ ͦ C, while zinc is 39.15949 mV/ ͦC, and copper is 1.72348 mV/ ͦC.